Gestational changes in buprenorphine exposure: A physiologically‐based pharmacokinetic analysis. (21st June 2018) - Zhang, Hongfei; Kalluri, Hari V.; Bastian, Jaime R.; Chen, Huijun; Alshabi, Ali; Caritis, Steve N.; Venkataramanan, Raman
Abstract : Aims: Buprenorphine (BUP) is approved by the US Food and Drug Administration for the treatment of opioid addiction. The current dosing regimen of BUP in pregnant women is based on recommendations designed for nonpregnant adults. However, physiological changes during pregnancy may alter BUP exposure and efficacy. The objectives of this study were to develop a physiologically‐based pharmacokinetic (PBPK) model for BUP in pregnant women, to predict changes in BUP exposure at different stages of pregnancy, and to demonstrate the utility of PBPK modelling in optimizing BUP pharmacotherapy during pregnancy. Methods: A full PBPK model for BUP was initially built and validated in healthy subjects. A fetoplacental compartment was included as a combined compartment in this model to simulate pregnancy induced anatomical and physiological changes. Further, gestational changes in physiological parameters were incorporated in this model. The PBPK model predictions of BUP exposure in pregnancy and during the postpartum period were compared to published data from a prospective clinical study. Results: The predicted BUP plasma concentration–time profiles in the virtual pregnant populations are consistent with the observed data in the 2 nd and 3 rd trimesters, and the postpartum period. The differences in the predicted means of dose normalized area under the plasma drug concentration–time curve up to 12 h, average concentration and maximum concentration were within ±25% of the corresponding observed means with the exception of average concentration in the 3 rd trimester (–26.3%). Conclusion: PBPK model‐based simulation may be a useful tool to optimize BUP pharmacotherapy during pregnancy, obviating the need to perform pharmacokinetic studies in each trimester and the postpartum period that normally require intensive blood sampling.